Advancing Quality Standards in Mixed Methods Research: Extending the Legitimation Typology. (January 2023) - Perez, Analay; Howell Smith, Michelle C.; Babchuk, Wayne A.; Lynch-O'Brien, Louise I.
Several scholars have proposed frameworks for assessing the quality of mixed methods research (MMR) studies. However, no general consensus has emerged. The legitimation typology developed by Onwuegbuzie and Johnson (2006) is one promising approach that addresses quantitative, qualitative, and MMR elements. The aim of this intrinsic, exploratory case study is to explore the use of the legitimation typology in empirical MMR studies and through interviews with the developers, MMR scholars, and researchers who applied the legitimation typology to an empirical MMR study. We conducted a systematic methodological review using multiple databases and identified 49 empirical MMR studies that addressed the legitimation typology. Using a critical case sampling approach defined by participants' unique experiences with the legitimation typology, semi-structured interviews were conducted with five authors of empirical MMR studies, a mixed methods researcher who has written about the typology, and one of the authors of the original legitimation typology to expand on ways the legitimation typology is used in practice. Four overarching themes were identified: (a) comprehensive approach to assessing quality, (b) researchers' interpretation of legitimation types, (c) value of divergent findings, and (d) strategies for applying the legitimation typology. This case study adds to the MMR literature by clarifying the use of emic-etic and conversion legitimations and by proposing a new legitimation type: divergent findings legitimation. Hence, this study elucidates the application of one quality framework (i.e., legitimation) in MMR and provides recommendations to the field to further advance discussions on quality criteria and their implementation in mixed methods research.